Practical application of the flipped classroom technology in teaching translation to technical students - Beznis, Y. V.; Lapko, O. A. (Томский политехнический университет, 2023)
The article discusses the possibilities of using the innovative technology of flipped classroom in introducing theoretical topics in the discipline «Translation of specialized technical literature» to non-linguistic university students which lead to a significant improvement in the quality of language training and an increase in the effectiveness of the educational process.